Corpus of Mesopotamian Anti-Witchcraft Rituals Glossaries and Indices - Buylaere, Greta Van, (Ancient Magic and Divination;, 2020)
Among the most important sources for understanding the cultures and systems of thought of ancient Mesopotamia is a large body of magical and medical texts written in the Sumerian and Akkadian languages. An especially significant branch of this literature centres upon witchcraft. Mesopotamian anti-witchcraft rituals and incantations attribute ill-health and misfortune to the magic machinations of witches and prescribe ceremonies, devices, and treatments for dispelling witchcraft, destroying the witch, and protecting and curing the patient. The Corpus of Mesopotamian Anti-Witchcraft Rituals aims to present a reconstruction of this body of texts; it provides critical editions of the relevant rituals and prescriptions based on the study of the cuneiform tablets and fragments recovered from the libraries of ancient Mesopotamia.